One-tube post-PCR fluorescent labeling of DNA fragments. - Inazuka, M; Tahira, T; Hayashi, K (Genome Research, 1996)
A method for fluorescent postlabeling of PCR products has been developed. The method uses Klenow fragment of DNA polymerase I that exchanges the 3'-terminal residue of PCR-amplified DNA fragment for fluorescent nucleotides. All reactions, including PCR, are performed in one tube simply by successive addition of reagents. The products can be applied directly to fluorescence-based automated DNA sequencers without purification for either length determination in denaturing electrophoresis or mutation detection in SSCP electrophoresis.